E-SERVICE QUALITY IN POPULATION ADMINISTRATION SERVICES THROUGH THE E-OPEN APPLICATION - Ramadhan, Rendy; Bintari, Antik (Jurnal Governansi, 2025)
Public services in the era of Society 5.0 encourage the government to make breakthroughs in e-service. Problems with e-service quality that are not optimal in the e-service implementation process through the e-Open application, such as limited access, delays in service fulfilment, and system constraints in service application, are the background for this research. Based on these problems, an in-depth study is needed to provide a more comprehensive picture of the quality of e-service in implementing the e-Open application in Bekasi City. This research discusses the quality of e-service in population administration services through the e-Open application in Bekasi City in 2023. This research uses the e-service quality theory proposed by Parasuraman, Zeithal, and Malhotra (2005), which uses four dimensions: efficiency, fulfilment, system availability, and privacy. This research uses a mixed research method with a concurrent embedded strategy design and a purposive sampling technique. In addition, purposive and snowball techniques are used to determine informants. The results of this study indicate that research on the quality of e-service of population administration services through the e-open application based on the dimensions of efficiency and privacy is in a good category, while the dimensions of fulfilment and system availability are in the neutral category. However, the results of qualitative research indicate that there are still access limitations, service fulfilment that is often interrupted, and system constraints. The conclusion obtained from the results of this study is that although the quantitative results do not show a lousy category, the data has a medium and even high data distribution. This shows that some respondents in low numbers experience problems. However, the government also strives to provide quality e-service for the community so that this application can run and develop and be valued by the community.